Improving Elementary Students’ Computational Thinking Skills through an Educational Robot Intervention: A Quasi-Experimental Study - Yang, Siou-Yu; Lin, Yi-Chun; Lin, Yen-Ting (International Journal of Learning, Teaching and Educational Research, 2024)
Globally, many educational institutions recognize the importance of computational thinking and have begun incorporating it into primary education. Educators cultivate students’ computational thinking skills through block-based programming; however, a lack of digital learning tools that offer real interaction may negatively impact students’ computational thinking learning performances. This study proposes a cost-effective, block-based, programmable computational thinking educational robot developed using the open-source Arduino platform, combined with Android application development. This robot is specifically designed for use in elementary computational thinking education. To assess the impact of the proposed approach on elementary students’ learning achievement, motivation, and attitudes towards computational thinking education, a quasi-experimental design with control and experimental groups was implemented in the computational thinking curriculum at an elementary school. The experiment was conducted over a period of three weeks and involved two classes of students and one teacher. The control group engaged in computational thinking learning activities using computers, while the experimental group completed computational thinking learning activities using the computational thinking educational robot and application developed in this study. Data were collected through prior knowledge tests of computational thinking, learning motivation and attitude questionnaires, and computational thinking achievement tests completed by the students. The results indicate that the experimental group outperformed the control group in learning achievement, motivation, and attitudes, demonstrating that physical interaction in learning can effectively enhance learning performances. https://doi.org/10.26803/ijlter.23.9.18